Ethanol Alters Proliferation and Differentiation of Normal and Chromosomally Abnormal Human Embryonic Stem Cell‐Derived Neurospheres. (21st May 2013) - Krishnamoorthy, Malini; Gerwe, Brian A.; Scharer, Christopher D.; Sahasranaman, Vanita; Eilertson, Carmen D.; Nash, Rachel J.; Usta, Sümeyra Naz; Kelly, Shasmine; Rose, Matthew; Peraza, Rene; Arumugham, Jagan; Stewart, Bethany; et al.
<x xml:space="preserve">Abstract</x> Ethanol is a powerful substance and, when consumed during pregnancy, has significant psychoactive and developmental effects on the developing fetus. These abnormalities include growth retardation, neurological deficits, and behavioral and cognitive deficiencies, commonly referred to as fetal alcohol spectrum disorder. The effect of ethanol has been reported to affect cellular development on the embryonic level, however, not much is known about mutations contributing to the influence of ethanol. The purpose of our study was to determine if mutation contribute to changes in differentiation patterning, cell‐cycle regulatory gene expression, and DNA methylation in human embryonic stem cells after ethanol exposure. We exposed human embryonic stem cells (with and without know DNA mutations) to a low concentration (20 mM) of ethanol and measured neurosphere proliferation and differentiation, glial protein levels, expression of various cell‐cycle genes, and DNA methylation. Ethanol altered cell‐cycle gene expression between the two cell lines; however, gene methylation was not affected in ether lines.. Birth Defects Res (Part B) 98:283–295, 2013. © 2013 Wiley Periodicals, Inc.